Hepatocyte Nuclear Factor 3β Plays a Suppressive Role in Colorectal Cancer Progression - Wang, Juan; Lu, Hao; Wang, Wei; Zheng, Nanxin; Wang, Yi; Hu, Zhiqian; Ji, Gang (Frontiers in Oncology, 2019)
Background and objective: Hepatocyte nuclear factor 3β (HNF3β) is a key transcription factor in the development of the gastrointestinal tract. However, only few studies have examined its’ expression, function and potential clinical significance in colorectal cancer tumorigenesis and progression. Methods: HNF3β expression in colorectal cancer tissue samples of 174 patients was assessed by immunohistochemistry. The results were analyzed with respect to patients’ clinicopathological characteristics and survival. Following the in vitro cell transfection, MTT, wound healing, and Transwell assays were used to test cell proliferation, migration, and invasion respectively. Western blot was used to examine IL6, JAK1 and STAT3 protein expression. The potential for tumor formation was evaluated using a mouse xenograft model. Results: HNF3β expression was lower in colon cancer tissue compared to normal tissue and correlated with UICC clinical stage (P = 0.001), depth of invasion (P = 0.004), regional lymph node metastasis (P = 0.007), distant metastasis (P = 0.048) and poor survival (P < 0.001) in patients with colorectal cancer. Furthermore HNF3β overexpression impeded proliferation, migration and invasion of SW480 cells via JAK-STAT3 signaling in vitro. Moreso, HNF3β overexpression showed a significant growth inhibition of subcutaneous xenograft tumors in vivo. Conclusions: The results show that HNF3β acts as a suppressor of colorectal cancer progression and decreased HNF3 β expression is closely related to the poor prognosis. Thus, HNF3β may be a potential molecular target for inhibition of colorectal cancer cells and development of new anti-tumor therapies.